Error Analysis of English Vowels Pronunciation Made by The Students of English Education Study Program - Rullu, ST Marhana; Nggolaon, Desriani; Budahu, Nurviana (Qalam : Jurnal Ilmu Kependidikan, 2023)
Study Program in Universitas Muhammadiyah Luwuk. This study used qualitative method in describing data. The data were obtained list of vocabularies and interviews on the research subject. The researchers compared based on the transcription there are 12 vowels in monophthong, 8 in diphthong, and 5 in triphthong. The result of this study, they made error vowels pronunciation as many as 10 in monophthong, they are: /iː/,/ɪ/,/e/,/æ/,/ə/,/ɜː/,/ʌ/,/ɑː/,/ʊ/,/uː/. They made error vowels pronunciation as many as 5 in diphthong, they are: /eɪ/,/aɪ/,/aʊ/,/ɪə/,/eə/. And they are made error vowels pronunciation as many as 3 in triphthong, they are: /aɪə/,/əʊə/,/eɪə/. The cause of error by expert, they are caused by carelessness, first language interference, translation. And in this study, the researcher found another cause of error they are lack of knowledge and accent.